Association of P53 codon 72 polymorphism and ameloblastoma - N. Kitkumthorn (2018)
Objective: To test the hypothesis that P53 codon 72 polymorphism was associated with an increased risk of developing ameloblastoma in the Thai population. Materials and methods: Seventy-eight ameloblastomas and 94 healthy controls were genotyped for the P53 codon 72 by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Results: The frequencies of the ArgArg, ArgPro and ProPro genotypes were 28.72%, 50.00% and 21.28%, respectively, in the controls; and 44.87%, 51.28% and 3.85%, respectively, in ameloblastomas. Therefore, P53 Arg is an ameloblastoma- susceptible allele [OR (95% CI) = 2.06 (1.28-3.31), P = 0.002]. Sex-adjusted OR (95% CI) is 2.08 (1.29-3.34), P = 0.002; and adjusted OR by clinical type (95% CI) is 2.04 (1.34-3.13), P < 10-3. Therefore, the increased risk associated with P53 Arg may not be influenced by either the sex of patients or clinical characteristics of the tumours. Moreover, when compared with homozygous P53 Pro, people who carried the Arg allele had a remarkably high risk of developing ameloblastoma [adjusted OR (95% CI) = 7.26 (2.34-23.41), P < 10-3]. Conclusion: The Arg allele of P53 gene codon 72 may increase susceptibility, and P53 may be important in the aetiology of ameloblastoma. © 2010 John Wiley & Sons AS.